Examining The Leg Muscles' Explosive Powers Impact to Smash in Female Volleyball Athletes - Insanistyo, Bayu; Kurniawan, Edi; Nopiyanto, Yahya Eko; Ibrahim, Ibrahim; Kardi, Ipa Sari (Physical Activity Journal (PAJU), 2023)
Leg muscle explosive power is important in someones success in doing smashes in volleyball games. This study reveals the leg muscles explosive power and smash ability level and determines the correlation between the two variables. The method used is descriptive quantitative with a correlation approach. The population in this study were all female volleyball extracurricular participants at SMK Negeri 4 Lubuklinggau City. Data collection techniques and instruments used vertical jump tests and volleyball smash tests. Data analysis using SPSS software showed that leg muscle explosive power was at a low level of as much as 56%, smash ability was at a moderate level of as much as 37%, and a good level of as much as 7%, and there was a significant positive relationship. From the results of this study, it is recommended that extracurricular coaches develop training programs that can increase muscle explosive power